Pisa syndrome in Idiopathic Normal Pressure Hydrocephalus - Todisco, Massimiliano; Pozzi, Nicolò Gabriele; Zangaglia, Roberta; Minafra, Brigida; Servello, Domenico; Ceravolo, Roberto; Alfonsi, Enrico; Fasano, Alfonso; Pacchetti, Claudio (Parkinsonism & related disorders, 2019)
Idiopathic Normal Pressure Hydrocephalus (iNPH) is a complex syndrome of ventriculomegaly that can include parkinsonian-like features besides the classical triad of cognitive decline, urinary incontinence, and gait/balance disturbances. Pisa syndrome (PS) is a postural abnormality often associated with parkinsonism and defined as lateral trunk flexion greater than 10° while standing that resolves in the supine position. We reported a case series of classical “fixed” PS and one case of “Metronome” recurrent side-alternating PS in iNPH, displaying opposite electromyographic patterns of paraspinal muscles. Eighty-five iNPH patients were followed longitudinally for at least one year through scheduled clinical and neuropsychological visits. Five (5.9%) subjects revealed PS. None of them had nigrostriatal dopaminergic involvement detected by [123I]FP-CIT SPECT. Among these patients, four had “fixed” PS, whereas one showed a recurrent side-alternating PS which repeatedly improved after ventriculo-peritoneal shunt and following adjustments of the valve-opening pressure of the shunt system. This is the first case series of PS in iNPH and the first report of “Metronome” PS in iNPH. The prompt response of the abnormal trunk postures through cerebrospinal fluid (CSF) shunt surgery suggests a causative role of an altered CSF dynamics. PS and gait disorders in iNPH could be explained by a direct involvement of cortico-subcortical pathways and subsequent secondary brainstem involvement, with also a possible direct functional damage of the basal ganglia at the postsynaptic level, due to enlargement of the ventricular system and impaired CSF dynamics. The early detection of these cases supports a proper surgical management. •Motor phenomenology of iNPH can include parkinsonian features.•Pisa syndrome is a severe postural abnormality often associated with parkinsonism.•Five out of eighty-five iNPH patients showed Pisa syndrome.•One iNPH patient manifested a recurrent side-alternating Pisa syndrome.•Pisa syndrome in iNPH can improve after shunt surgery.